RARE CAUSES OF ISCHEMIC STROKE. FEATURES OF ACUTE STROKE IN PATIENTS WITH DISSECTION OF THE GREAT VESSELS - I. P. Dudanov; N. O. Vasilchenko; M. A. Askerov; O. V. Rubleva; D. V. Merkulov; V. V. Akhmetov; O. M. Shulga; M. O. Telukhina (Исследования и практика в медицине)
Purpose of the study. Identification of the main causes of ischemic stroke in patients with aortic dissection, features of the clinical picture, the choice of optimal tactics for the management of such patients.Patients and methods. During 2017, 11 patients with aortic dissection were hospitalized for emergency indications and underwent complex, surgical interventions. In 4 patients, the reason for hospitalization was ischemic stroke, in 7 patients, the onset of the disease was manifested by chest pain. Subsequently, in all cases, ischemic stroke developed within 48 hours from the onset of pain symptoms. Fatal outcomes occurred in 5 (45.45%).Results. All patients were operated on for aortic dissection. Various types of surgery were performed. The best results were achieved with a hybrid operation — prosthetics of the aortic arch with endoprosthetic replacement of the descending aorta. The main reason for the development of ischemic stroke with aortic dissection and surgery for its elimination is the development of brain malfunction. The cause of death was the dissemination of the dissection into the visceral arteries with the development of multiple organ failure or aortic rupture of the aorta with hemo tamponade.Conclusion. As a rule, several pools of blood supply to the brain, episodes of psychomotor excitement are involved in the dissection of the aorta and branches of the aortic arch, cognitive impairments are progressing, since cortical branches of the brain are usually involved. With the timely assignment of neuroprotective therapy, revascularization, early complex rehabilitation, there is a significant positive dynamics of neurological status, restoration of cognitive functions.